NEONATAL LIPID LEVELS - CAN THEY BE A BENCHMARK FOR LIPID LOWERING IN ADULTS? - KA, SUDHARSHANA MURTHY; BHANDIWAD, AMBARISHA; MURTHY KVKSN,; SHIVANI AGGARWAL, (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Background: Cord blood lipid estimation in healthy newborns is an opportunity to assess lipid profile parameters at the beginning of life and this might serve as a guide for determining the minimum levels of cholesterol and other lipoprotein required for maintaining normal bodily physiological functions. Various lipid parameters are targeted by interventions in adults in the management of atherosclerotic coronary artery diseases be it for primary prevention or secondary prevention. The guidelines recommend reduction of LDL-C to less than 70mg% in high risk group individuals. The impact of these low levels of lipids on physiological functions of tissues is a concern to be answered. Hence it's hypothesized that probably the lipids at birth in healthy newborns are the bare minimum required to maintain the normal physiological bodily metabolism. Hence this study was conceived. Objectives: The present study is to determine the baseline lipid profile at birth in healthy newborns and indirectly to ascertain the minimum level to which lipids can be lowered in adults by therapeutic interventions. Further we also explored the influence of maternal factors on cord blood lipid parameters. Methods: The study group consisted of 100 term newborns and their mothers. Cord blood and fasting maternal serum samples were analysed for lipid profile, blood sugar and HbA1c estimation. Mean and standard deviations were calculated. Paired t test and ANOVA test of variance were applied to compare lipid profile parameters of mother with the cord blood. Results: Lipid profile parameters were significantly low in cord blood. Mean LDL cholesterol in cord blood was 36.63mg/dl ,mean triglycerides was 49.38mg/dl, mean total cholesterol was 73.83mg/dl, mean HDL cholesterol was 21.13mg/dl, mean LDL/HDL was 1.84 and mean total cholesterol/HDL cholesterol was 3.74 .Cord blood lipid parameters were significantly altered in mothers with dyslipidemia, diabetes and hypertension. Conclusion: This study has revealed a LDL-C level of 36.63mg% in healthy term newborns. Reducing LDL-C to <70mg% may not interfere with physiological bodily metabolism in adults as hypothesized, but reducing it to a level less than 35mg% may interfere with normal bodily metabolism. Key Words: Neonatal lipids, Maternal lipids, cord blood lipids, Lipid lowering therapy, Lipid and normal metabolism